1993
DOI: 10.1038/364735a0
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase V is a relative of eukaryotic topoisomerase I from a hyperthermophilic prokaryote

Abstract: The DNA topoisomerases are ubiquitous enzymes that fulfil vital roles in the replication, transcription and recombination of DNA by carrying out DNA-strand passage reactions. Here we characterize a prokaryotic counterpart to the eukaryotic topoisomerase I in the hyperthermophilic methanogen Methanopyrus kandleri. The new enzyme, called topoisomerase V, has the following properties in common with eukaryotic topoisomerase I, which distinguish it from all other known prokaryotic topoisomerases: (1) its activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
83
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 17 publications
0
83
0
Order By: Relevance
“…Some of the (HhH) 2 domains are involved in DNA repair, and there are at least two apurinic/apyrimidinic site-processing active sites (31,33). Topo-V displays many characteristics similar to those of type IB enzymes; it can relax positively and negatively supercoiled DNA, forms a transient covalent bond with the 3Ј end of the broken DNA, does not require magnesium for activity, and relaxes DNA by a swiveling mechanism (7,10,34). The most striking differences, which place Topo-V in an entirely different subtype, are the distinct domain organization with two different DNA processing activities, the unique structure of the topoisomerase domain, and the lack of sequence similarity with any other topoisomerase subtype (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the (HhH) 2 domains are involved in DNA repair, and there are at least two apurinic/apyrimidinic site-processing active sites (31,33). Topo-V displays many characteristics similar to those of type IB enzymes; it can relax positively and negatively supercoiled DNA, forms a transient covalent bond with the 3Ј end of the broken DNA, does not require magnesium for activity, and relaxes DNA by a swiveling mechanism (7,10,34). The most striking differences, which place Topo-V in an entirely different subtype, are the distinct domain organization with two different DNA processing activities, the unique structure of the topoisomerase domain, and the lack of sequence similarity with any other topoisomerase subtype (8,9).…”
mentioning
confidence: 99%
“…Until recently, only two subtypes of type I topoisomerases had been identified, type IA and IB. A third subtype, type IC, was added with the discovery and characterization of Methanopyrus kandleri topoisomerase V (Topo-V) 2 (7)(8)(9). The three type I subtypes are very different in sequence and structure, although type IB and type IC molecules share some overall mechanistic similarities (10).…”
mentioning
confidence: 99%
“…In vitro formation of covalent Topo V-DNA complexes involving regular duplex DNA is, however, very inefficient. The one cleavage site mapped so far resembles the consensus site for DNA cleavage by eukaryotic topoisomerase I in the absence of camptothecin (1).…”
mentioning
confidence: 99%
“…This results in the formation of a phosphotyrosine bond between the enzyme and the 3Ј end of the broken strand. This covalent intermediate can be trapped by denaturing the enzyme during catalysis with either SDS or alkali (1,9). In vitro formation of covalent Topo V-DNA complexes involving regular duplex DNA is, however, very inefficient.…”
mentioning
confidence: 99%
“…Our results showed that even though eukaryotic topoisomerases I can in general relax both positively and negatively supercoiled DNA, their action on DNA may result in different superhelical states. A prokaryotic enzyme DNA topoisomerase V has been purified from the hyperthermophilic methanogen Methanopyrus kandleri and found to be related to eukaryotic topoisomerase I [31]. It relaxes both positively and negatively supercoiled DNA but prefers positively over negatively supercoiled substrates [32].…”
Section: Discussionmentioning
confidence: 99%